Enhanced ductility by Mg addition in the CNT/Al-Cu composites via flake powder metallurgy. (March 2021) - Yuan, Chao; Zhang, Zhiming; Tan, Zhanqiu; Xu, Lang; Zhang, Shuyan; Fan, Genlian; Zhang, Peng; Li, Zhiqiang
Graphical abstract: Highlights: Mg addition disrupted native oxide layers and improved interfacial bonding. Mg addition transformed continuous Al2 O3 layer into dispersed spinel MgAl2 O4 nanoparticles. Almost two times of ductility with little strength loss was achieved by Mg addition in CNT/Al-Cu. Abstract: The inevitable native oxide layer is a critical issue to achieve high mechanical performance of CNT/Al-alloy composites, especially prepared by powder metallurgy. Here, an easy strategy was proposed to avoid and eliminate the negative effect of native oxide (Al2 O3 ) layer by Mg addition, and significant improvement of ductility was achieved in the CNT/Al-Cu composite. Native Al2 O3 remained as continuous layers around CNTs or clusters of fragments in the CNT/Al-Cu without Mg addition. Mg addition transformed the native Al2 O3 layer into spinel MgAl2 O4 nano-phases dispersed both inside grains and on the interfaces. It is supposed that this transformation of oxide layer could improve the interfacial bonding due to Al-Al and Al-CNT direct interfacial contact. As a result, compared with CNT/Al-Cu composites, the tensile strength only changed a little, however, almost two times of fracture ductility was achieved by Mg addition in the final composites.